2023
DOI: 10.1021/acschemneuro.3c00180
|View full text |Cite
|
Sign up to set email alerts
|

Role of Imaging Modalities and N-Acetylcysteine Treatment in Sepsis-Associated Encephalopathy

Abstract: Sepsis-associated encephalopathy is a severe systemic infection complication. Although early stages involve pathophysiological changes, detection using conventional imaging is challenging. Glutamate chemical exchange saturation transfer and diffusion kurtosis imaging can noninvasively investigate cellular and molecular events in early disease stages using magnetic resonance imaging (MRI). N-Acetylcysteine, an antioxidant and precursor of glutathione, regulates neurotransmitter glutamate metabolism and particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Due to the multiple interactions between the ER stress pathway and the inflammatory response, the underlying mechanisms by which NAC plays a role in sepsis-induced muscle atrophy deserve further investigation. As mentioned previously, NAC is a potential H2S-releasing donor [18,23]. Ferlito et al elucidated that H2S inhibits CHOP expression and improves survival in septic mice [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the multiple interactions between the ER stress pathway and the inflammatory response, the underlying mechanisms by which NAC plays a role in sepsis-induced muscle atrophy deserve further investigation. As mentioned previously, NAC is a potential H2S-releasing donor [18,23]. Ferlito et al elucidated that H2S inhibits CHOP expression and improves survival in septic mice [45].…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylcysteine (NAC), a precursor of glutathione (GSH), has anti-inflammatory, antioxidant, and cytoprotection properties, and it is deacetylated intracellularly to form L-cysteine and acts as potential H2S-releasing donor [18][19][20]. NAC protects against sepsisassociated encephalopathy, septic acute lung injury, and septic acute kidney injury, and its mechanism of action is related to anti-inflammatory, antioxidant, and anti-apoptotic functions [21][22][23]. Recently, a study found that NAC prevented skeletal muscle atrophy in diabetes [24].…”
Section: Introductionmentioning
confidence: 99%